LINGKUNGAN HIDUP DENGAN KETERAMPILAN MENULIS BERITA SISWA KELAS VIII SMP NEGERI 22 PADANG - Muhammad, Satria Agung; Ermanto, Ermanto; Zulfikarni, Zulfikarni (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2016)
ABSTRACTÂ There are objectives of this research. First, describing the control of vocabulary environment area at students grade VIII SMP Negeri 22 Padang. Second, describing the writing skill of news text at student grade VIII SMP Negeri 22 Padang. Third, describing the relation vocabulary environment area with the skill in writing news text at student grade VIII SMP Negeri 22 Padang. This is a quantitative research with descriptive method and using correlational research design. Population and sample of this research are VIII th grade student of SMP Negeri 22 Padang consist of 142 students and 36 sample students. This research use Simple random Sampling technique. This experiment consists of two variables: vocabulary as the independent variable (X) and the writing skills of news text as a dependent variable (Y). Data research was score on result of control vocabulary test and score on writing skills of news text. Data that has been collected were analyzed with indicator to get score and students value. The research instrument is an objective test to meassure vocabulary mastery and test to measure the performance of the writing skills of news text. Based of result data analyzed and explanation, were concluded 3 case. First, control of vocabulary on environment area students grade at VIII SMP Negeri 22 Padang was on good qualification (77,43). Second, writing skills of news text at student grade VIII SMP Negeri 22 padang was on good qualification (79,01). Third, control vocabulary on environment area corresponded with writing skills news text at students grade SMP Negeri 22 Padang. Nevertheless, for the writing skills news text were needed control of vocabulary on environment area.Â Kata Kunci : hubungan, penguasaan, berita, menulis